Characterization of fibrillated antioxidant whey protein hydrolysate and comparison with fibrillated protein solution. (January 2016) - Mohammadian, Mehdi; Madadlou, Ashkan
Abstract: Whey proteins were hydrolyzed to reach maximum in vitro antioxidant activity, followed by fibrillation via heating at pH 2.0. Heating of either whey protein isolate (WPI) or its antioxidant hydrolysate (WPH) formed fibrillar structures with diameters < 10 nm and increased the antioxidant activity. Based on microscopic images and circular dichroism spectroscopy it was concluded that fibrillation potency of WPH was inferior to WPI due likely to the enzymatic destruction of α-helix structures and that antioxidant WPH yielded much less uni-sized fibrils in length than WPI solution. SDS-PAGE analysis proposed that proteins enzymatic hydrolysis prior to acidic hydrolysis during fibrillation process results in a heterogenous mixture of peptides that interfere with and limit the fibrillation of WPH. Fourier transform infra-red spectroscopy suggested a more extensive disruption of hydrogen bonds than their formation once WPI was fibrillated. The fibrillated antioxidant WPH was less shear-thinning (higher n index value) and consistent (i.e. lower K value), and more soluble (at ∼ pI) than fibrillated WPI. Foam stability of WPI and WPH improved upon fibrillation. Graphical abstract: Highlights: Whey protein isolate (WPI) and its antioxidant hydrolysate (WPH) were fibrillated. Fibrillation increased the antioxidant activity of both WPI and WPH. AFM imaging and CD spectroscopy suggested inferior fibrillation of WPH to WPI. The foam stability and viscosity of the antioxidant WPH augmented by fibrillation.